Song and dance: a memetic angle on the evolution of musicality and music via case studies of a musemeplex in Saint-Saëns and ABBA - Jan, Steven (Frontiers in Psychology, 2024)
Applying the theory of memetics to music offers the prospect of reconciling general Darwinian principles with the style and structure of music. The nature of the units of cultural evolution in music -memes or, more specifically, musemes -can potentially shed light on the evolutionary processes and pressures attendant upon early-hominin musicality. That is, primarily conjunct, narrow-tessitura musemes (those conforming to Ratner's "singing style", and its instrumental assimilations) and primarily disjunct, wide-tessitura musemes (those conforming to Ratner's "brilliant style", and its vocal assimilations) appear to be the outcome of distinct cultural-evolutionary processes. Moreover, musemes in each category arguably acquire their fecundity (perceptualcognitive salience, and thus transmissibility) by appealing to different music-underpinning brain and body subsystems. Given music's status as an embodied phenomenon, both singing-style and brilliant-style musemes recruit and evoke image schemata, but those in the former category draw primarily upon vocal images of line, direction and continuity; whereas those in the latter category draw primarily upon rhythmic impetus and energy. These two museme-categories may have been moulded by distinct biological-evolutionary processes -the evolution of fine vocal control, and that of rhythmic synchronisation, respectively; and they might -via the process of memetic drive -have themselves acted as separate and distinct selection pressures on biological evolution, in order to optimise the environment for their replication. As a case-study of (primarily) singing-style musemes, this article argues that a passage from the love duet "Mon coeur s'ouvre à ta voix" from Camille Saint-Saëns' opera Samson et Dalila op. 47 (1877) is the cultural-evolutionary antecedent of the Introduction/Chorus/Outro material of ABBA's song "The Winner Takes It All". Discussion of their melodic and harmonic similarities supports a memetic link between elements of Saint-Saëns' duet and ABBA's song. These relationships of cultural transmission are argued to have been impelled by the fecundity of the shared musemes, which arises from the image-schematic and embodied effects of the implication-realisation structures (in Narmour's sense) that comprise them; and which is underwritten by the coevolution of musemes with vocal-and rhythmic-production mechanisms, and associated perceptual-cognitive schemata.